Morphometric analysis of the foramen spinosum and variations of its shape, number, and relation to the spine of the sphenoid bone - Misganaw Gebrie Worku; Edward Clarke (Elsevier, 2021)
Background: The foramen spinosum (FS) transmits the middle meningeal vessels and meningeal branches of the mandibular nerve. The anatomical variation of FS is of great clinical significance in tumor detection and abnormal bony growth. This study aimed to assess morphometric measurements of the foramen spinosum and its variation in shape, number, and position to the sphenoid spine. Methods and materials: An anatomical study was conducted on 64 adult skulls. The study material involved human macerated Ethiopian skulls. Using a screw-adjusted compass and Vernier calipers, all measurements were taken. The area of the foramen spinosum was determined using formula A= (π x L x B)/4[π = 3.14, L = length, B = width]. The mean (±SD) was calculated for all the measurements. SPSS version 20 software was used to analyze the data, and P < 0.05 was regarded as statistically significant. An independent tt-test was applied to assess the mean difference in length and width of foramen spinosum between the right and left sides. Results: the mean anteroposterior (AP) diameter of the foramen spinosum was 3.72 ± 1.33 mm and 3.37 ± 1.26 mm on the right and left sides, respectively. The mean transverse diameter was 3.3 ± 1.19 mm on the right side and 2.97 ± 1.9 mm on the left side. An independent t-test proved no significant difference between the sides of the skulls and anteroposterior or transverse FS diameters. Conclusion: The mean diameter of the foramen spinosum was larger than reports from other previous studies. An independent t-test indicates there are no statistically significant mean differences between both sides of the skulls. Therefore, it is advisable to understand the variations of the foramen spinosum for surgeons who approach the middle cranial fossa for different procedures.